Quantifying heat stress of sauna suits during physical activity and examining the effects of heat acclimation on physiological responses in hypoxic conditions: a preliminary explorative study on cross-adaptation - Carrillo, S. N.; Pina, E.; Buchanan, C. A.; Dalleck, L. C. (International Journal of Research in Exercise Physiology, 2020)
Purpose: The purpose of this study was two-fold: to analyze thermal stress of sauna suits during low-moderate exercise; and to examine the effects of a two-week heat acclimation training with a sauna suit on physiological responses in hypoxic conditions in active males. Methods: 4 physically active males (M=24 ± 2.7 yrs) completed a two-week, heat acclimation period using a sauna suit. Hypoxic testing took place pre- and post- heat acclimation, involving 30 minutes of sitting while being exposed to simulated altitude (~4000 meters). Heart rate (HR), oxygen saturation (SpO2), blood pressure (BP), and symptoms of Acute Mountain Sickness were all measured. Subjects also completed 2 thermal stress tests, involving jogging for 45 minutes at their Ventilatory Threshold-1 with and without a sauna suit. Core temperature, HR, and SpO2 were measured during the thermal stress tests. Results: Significant differences (p<0.05) were found for mean arterial pressure comparing pre- to post- hypoxic tests with an average improvement of 9.22 ± 5.18 mm/Hg. No statistical mean differences were found for the other variables measured during the hypoxic tests, even though they all improved post- heat acclimation. Significant differences were found for area under the curve for core temperature comparing thermal stress test trials with an average increase in area under the curve of 42.53 ± 16.16 °F/min. There were no significant main effects for the other variables measured during the thermal stress tests but did show decrements that are expected with heat exposure. Conclusion: The results of this novel study support the use of a sauna suit as a form of heat acclimation to enhance physiological responses at altitude.